Sugar contents and physical characters of six leading date cultivars of southern Libya - AL-SHURAFA, MOHAMED Y.; AHMED, HUSAIN S.; NAGI, SAMIA A. (The Libyan Journal of Agriculture, 2023)
Six leading dale cultivars (Taleese, Taghiat, Tasfert, Adwi, Aspear. and Scloulou) at tamar stage, were collected from Al-Shatie, Sebha, and Ubari districts of southern Libya. Analysis of sugars showed that reducing sugars were the dominant form of sugars in all cultivars. Non-reducing sugars were relatively low or absent. The percentages of total sugars for the different cultivars were. 66.5-75.5 for Adwi. 67.1-74.4 for Taghiat. 63.0 74.7 for Seloulou, 64.0 74.0 for Aspear. 62.5-71.9 for Tasfert, and 62.7 70.2 for Taleese. A general conclusion was drawn that Libyan dates were as good as world leading cultivars in their sugar content. Physical characters of the fruits were also taken into account